On the Social Structure of Markets - William A. Jackson (Cambridge Journal of Economics, 2007)
Economic theorists have seldom discussed the social structures behind markets, even though market trading relies heavily on seller/buyer roles and personal relations among traders. This paper considers the structural basis of markets and proposes a layered approach which accommodates a wide range of competitive and relational trade within a definition of markets that distinguishes them from non-market exchange. Giving due regard to social structures lays bare the institutional character of markets and provides a rationale for case studies of how particular markets function.
Keywords: B4; D4; L1; 330; markets; social structure; agency; competition; rivalry